Image-guided localization of small lung nodules in video-assisted thoracic surgery - Zhao, Ze-Rui (J Thorac Dis, 2016)
The advancement of imaging technology has recently facilitated single port minimally-invasive thoracic surgery techniques. Cone-beam computed tomography (CBCT) shows promising results in visualizing the target lesion and its surrounding critical anatomy, with an error of less than 2 mm. The integration of CBCT with the operating room (OR) to form the hybrid OR, provides unparalleled real-time imaging of the patient, which can be used with electromagnetic navigation bronchoscopy to confirm successful navigation and increase procedural accuracy particularly for small peripheral pulmonary targets. Furthermore, implantation of hookwires or microcoils that are widely used to localize the lesion can take place in the hybrid suite, eliminating the common complications and discomfort associated with the conventional workflow carried out in the radiology suite. Displacement leading to localization failure can be also reduced, and sublobar resection will be performed without resecting a larger area of parenchyma than desired. This one-stop, paradigm-shifting concept for simultaneously diagnosing and managing small pulmonary lesions in the hybrid OR can lead to reduced invasiveness and improved patient care.